O desenvolvimento de agências na educação infantil bilíngue durante as aulas remotas na Pandemia da COVID-19 - Silva, Monika Garcia Campos da (2022)
This research aims to investigate the several types of agencies that were conducted from the proposals made during remote teaching in the Covid-19 pandemic for a group of bilingual early childhood education children. This teaching mode takes place through distance classes, via electronic devices, during the 2020 academic year due to social isolation and the closing of schools, in order to spread Covid-1 - an extremely lethal virus in the course of schools, millions of deaths around of the world. We start from the assumption that all subjects have agency, which gives them the ability to act in the world as producers of culture, assuming collective responsibilities and we present, as powerful proposals, Vygotsky's play, and social activities as a space for dialectical interaction between peers and teacher, so that we believe that they can stimulate the participation, responsibility, and commitment of subjects, developing the power of action in real situations. of their own lives. This study is based on the Theory of SocioHistorical-Cultural Activity, which recognizes and ensures, through dialogue and collaboration, the relationship between the subject, its historicity and its reality, in a cultural network, and it is linked to the performance researcher's professional in the bilingual segment of early childhood education, where immersion in the additional language (English) reaches involves the student in a contextualized way, entangled in situations that bring the child's reality into the classroom. The selected corpus is composed of the light of remote classes and the field diary of the teacher-researcher of the Critical Collaboration Research. The results show that the proposals that involve playing, make-believe and everyday activities arouse greater participation, decisionmaking power, and use of children’s experiential repertoire, providing opportunities for the development of themselves, others, and society